1997
DOI: 10.1097/00002800-199707000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Two Graduating Master's Students Struggle To Find Meaning

Abstract: This article was initiated to help two graduating Master's students learn what might be expected of them upon graduation. The purpose of this article is to provide insight from reviewing the current literature on clinical nurse specialist's (CNS's) characteristics. The authors believe that this information is especially useful for graduate CNS students and helpful for those who currently hold CNS positions. Based on a literature review, the article categorizes descriptions of the characteristics of the CNS rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Second, it has been suggested that effective communication (i.e. work environments that foster open communication between supervisors and employees) can reduce unclear situations and role conflict (McMyler and Miller, 1997). For example, in the presence of an open communication climate, nurses confronted with ambiguous situations and irreconcilable demands would be more likely to use adaptive coping strategies (Skinner and Edge, 2002), such as seeking information from their supervisor.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Second, it has been suggested that effective communication (i.e. work environments that foster open communication between supervisors and employees) can reduce unclear situations and role conflict (McMyler and Miller, 1997). For example, in the presence of an open communication climate, nurses confronted with ambiguous situations and irreconcilable demands would be more likely to use adaptive coping strategies (Skinner and Edge, 2002), such as seeking information from their supervisor.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…In general, the basic differences in role‐related perspectives between nurses and physicians and among nurses and other professional groups were shown to impede conflict resolution, if not an additional source of conflict. A review showed congruent expectations of the clinical nurse specialist’s (CNS) role by the CNS, management, staff nurses and physicians is important in avoiding negative conflict and other undesirable outcomes (McMyler & Miller 1997). A comparison of critical care physicians’ and nurses’ attitudes revealed discrepant views about the level of collaboration experienced (Thomas et al.…”
Section: Origins Of Conflict In Nursingmentioning
confidence: 99%
“…Similarly, inadequately delineated role functions, unrealistic expectations and limited recognition of clinical expertise complicated the role performance process (Bull & Hart 1995). The key solution to achieving congruent expectations of the advanced nursing role seems quite simple: clear communication (McMyler & Miller 1997). Without this, ambiguity, conflict and frustration can result.…”
Section: Role Stress In Advanced Practice Nursesmentioning
confidence: 99%